Pengaruh Lingkungan Kerja dan Stres Kerja Terhadap Kinerja Karyawan (Studi Kasus pada PT. Putra Nugraha Sentosa Mojosongo) - Isnaini, Khoirunnisa; , Drs. Ma'ruf, M.M (2015)
The aim of this research is to analyze effect of work environment and job stress on editorial staff performance at PT. Putra Nugraha Sentosa Mojosongo. Data in this research is primary data which got from questionnaire and secondary data PT. Putra Nugraha Sentosa Mojosongo. This research used multiply regression analysis and hypotheses testing done by t test and F test. Before analyzed by multiply regression and hypotheses testing, first, it had hold reliability and validity test. The result of this research show that the variable has a significant positive work environment on employee performance, meanwhile job stress variable has a significant negative effect on employee performance. Both the variable of work environment and job stress also affect the employee performance. This has been by the result of F test with the amount of 83,892. However, job stress are at low to moderate level will create a good employee performance and will worsen if the employee within a very long time and excessive.